Hubungan Pelaksanaan Discharge Planning dengan Tingkat Kecemasan dan Kesiapan Pulang pada Pasien Post Sectio Caesarea - Arif Annurrahman; Retno Koeswandari; Wiwin Lismidiati (PSIK FKKMK UGM, 2018)
Background: Fear of of post caesarean section (CS) pain and complication can be the sources of fear and anxiety for the mother during the puerperium period. Moreover, the relatively short length of stay for post-CS mothers cannot cover the entire length of care until the mother is cured. Discharge planning can improve patients and their families confidence in performing proper treatment independently after home arrival.Objective: To identify the correlation between discharge planning, anxiety level, and readiness for discharge among post-CS patients in Yogyakarta hospital.Methods: This quantitative research was a descriptive correlational study with cross sectional design. Respondents of this research were both, post elective and emergency CS patients who were hospitalized in a postpartum ward in a hospital in Yogyakarta. Thirty patients participated in this study. Readiness for Hospital Discharge Scale (RHDS), Hamilton Anxiety Rating Scale (HARS), and discharge planning overview questionnaire were used as research instruments in this research. Data were analyzed by Spearman Rank non-parametric correlation test.Results: More than half (70%) of total respondents had low discharge planning quality. Furthermore, most of the respondents (90%) had normal anxiety, and half of total respondents (53,3%) had moderate readiness for discharge. The correlation test showed there was no correlation between discharge planning and anxiety level (r=-0,008; p value = 0,967). However, there was a statistically significant correlation between discharge planning and readiness for discharge (r=0,434; p value = 0,017).Conclusion: There was a statistically significant correlation between discharge planning and readiness for discharge. In contrast, there was not any correlation between discharge planning and anxiety level of post CS patients. ABSTRAKLatar Belakang: Selama periode nifas, rasa takut akan nyeri dan komplikasi post-SC dapat menjadi sumber ketakutan dan kecemasan bagi ibu. Lama rawat inap ibu post SC yang relatif singkat tidak mampu mencakup keseluruhan perawatan sampai ibu sembuh. Pemberian discharge planning dapat meningkatkan kepercayaan diri pasien dan keluarga dalam perawatan mandiri setelah pulang ke rumah.Tujuan penelitian: Mengetahui hubungan gambaran discharge planning pada pasien post SC dengan tingkat kecemasan dan kesiapan pulang pasien di salah satu rumah sakit di Yogyakarta.Metode: Jenis penelitian ini adalah deskriptif korelasional dengan rancangan cross sectional. Sampel penelitian adalah semua pasien post SC baik elektif maupun emergensi yang dirawat inap di ruang post partum di salah satu rumah sakit di Yogyakarta. Jumlah responden penelitian adalah 30 orang dengan teknik purposive sampling. Instrumen yang digunakan antara lain Readiness for Hospital Discharge Scale (RHDS), Hamilton Anxiety Rating Scale (HARS), dan kuesioner gambaran discharge planning. Data dianalisis menggunakan uji korelasi non-parametrik Spearman Rank. Hasil: Lebih dari setengah responden (70%) memiliki kualitas discharge planning kurang, mayoritas responden (90%) memiliki kecemasan normal, dan mayoritas responden (53,3%) memiliki kesiapan pulang sedang. Uji korelasi menunjukkan tidak ada hubungan antara discharge planning dengan tingkat kecemasan (r=-0,008; p=0,967), namun ada hubungan discharge planning dengan tingkat kesiapan pulang (r=0,434; p=0,017).Kesimpulan: Terdapat hubungan antara discharge planning dengan tingkat kesiapan pulang namun tidak terdapat hubungan antara discharge planning dengan tingkat kecemasan pasien post SC.